Consumer Awareness of The Possibility of Using Payments with An NFC Chip Implanted Under the Skin – Polish Perspective - Michał OLEJNICZAK; Arkadiusz GRYKO (Communications of International Proceedings, 2022)
Payments using a microchip implanted under the skin debuted on the Polish market in the spring of 2021. At that time, the service provider began public relations activities aimed at familiarizing Poles with the new technology and the benefits of its use. Although Polish society is considered innovative and eagerly follows the news on the electronic payments market, in the first months of the start of sales, the service provider could not talk about success. This text is an attempt to answer the question of whether Poles were aware at that time that in their country it was already possible to pay using a chip implanted under the skin of the hand and whether they were aware of the existence of such technology at all. The authors made this attempt based on the conclusions of their own empirical research conducted in this period on a random sample (N=205) of adult Poles.
Keywords: contactless payments; NFC payments; payments with a chip implanted under the skin; consumer awareness